Analysis Of Supporting Factors For Work Readiness Of Final Semester Students Of Pgri University Semarang Class Of 2020 - Purwito, Aprilialeni; Efriyani Sumastuti,; M Fadjar Darmaputra, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to examine the influence of self-efficacy, soft skills, work interest, work motivation, and internship experience on work readiness of final semester students at PGRI University Semarang class of 2020. The research population was 2,140 final semester students from various faculties at PGRI University Semarang, with a sample 96 respondents were selected using accidental sampling techniques and measured using a Likert scale. The method used was quantitative with primary data from questionnaires, and analyzed using SPSS version 23 with multiple linear regression techniques. The results of research using the T test showed that the self-efficacy variable had a significant negative effect on work readiness. variable Soft skills, work interest, work motivation, and internship experience have a significant positive effect on work readiness.